Molecular dynamics study on the mechanical properties of nanocrystalline Ni-W alloys with bimodal structure. (1st December 2022) - Li, Guo; Wang, Ruipeng; Cai, Qixing; Zhang, Feng; Zhu, Dasheng; Li, Fengtian
Abstract: In order to study the effects of coarse grain size and Ni content on the mechanical properties, the molecular dynamics (MD) simulation of nanocrystalline (NC) Ni-W alloys with bimodal structure is carried out. The bimodal NC Ni-W alloys samples are established by embedding coarse grain into the fine grain matrix. The solute Ni atoms in the alloys are segregated in the grain boundary affected zone (GBAZ) through severe plastic deformation (SPD). The uniaxial tensile simulation of the samples shows that the coarse grain size and Ni content have obvious effects on the mechanical properties of bimodal NC Ni-W alloys. The dislocation activities and deformation mechanism of the NC Ni-W alloys are discussed in detail by observing the atomic configurations and strain evolutions diagrams obtained by MD simulation. At the same time, the phenomenon of Hall-Petch relationship and inverse Hall-Petch relationship is also observed in the research process.